Single-stage transformer less multilevel boost inverter with zero leakage current for PV system - Al-Mamoori, Dalya Hamzah; Ayob, Shahrin Md; Arif, M. Saad Bin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Transformer less inverters (TIs) are highly efficient and have a high power density, making them a popular choice for grid-connected solar PV applications. However, certain topologies can lead to high-frequency common-mode voltage (CMV), which can cause issues such as high leakage current, electromagnetic interference, and an absence of safety. Our newly developed inverter is designed to be more efficient, cost-effective, and compact than traditional types while also addressing the issue of leakage current. This architecture eliminates leakage current by directly connecting the grid's neutral terminal to the PV's negative polarity, resulting in a low leakage current. Moreover, the inverter increases output voltage using only one voltage source and a few power devices, making it a cost-effective solution. Its modular form allows for an increase in output levels, further enhancing its cost-effectiveness. We conducted a comprehensive mathematical examination, and the MATLAB/Simulink results demonstrate its ability to increase the output voltage, eliminate leakage current, and maintain acceptable output voltage THD and current waveforms. These results and the inverter's safety features showcase significant improvements over traditional inverters and provide a secure and reliable solution for grid-connected solar PV applications.